2015
DOI: 10.1136/jramc-2015-000498
|View full text |Cite
|
Sign up to set email alerts
|

The Hearts of Heroes: the epidemiology of cardiac disease in the UK Armed Forces

Abstract: When the general public look from the outside at the armed services, their impression is often one of earnest young men and women who are the pinnacle of physical fitness and health, and put their lives on the line for their country. There is usually sadness and respect for those killed on active operations, having put themselves in harm's way. Therefore, when the public discover that more than 1 in 10 deaths in the UK Armed Forces are due to cardiovascular disease, the air of sadness is invariably replaced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…UK data also demonstrate that the prevalence of death from CAD was higher than expected. 72 Other predictive models were tried in the past, as evident in the Prospective Army Coronary Calcium (PACC) trial 73,74 and found that in those over >40 years of age, the identification of CAC was associated with a 12-fold increase in cardiovascular events compared to conventional risk. Not only did CAC predict outcomes more accurately, it improved compliance with preventive therapy and lifestyle recommendations 73e77…”
Section: Evaluation Of Acute But Low Risk Chest Pain In the Emergencymentioning
confidence: 99%
“…UK data also demonstrate that the prevalence of death from CAD was higher than expected. 72 Other predictive models were tried in the past, as evident in the Prospective Army Coronary Calcium (PACC) trial 73,74 and found that in those over >40 years of age, the identification of CAC was associated with a 12-fold increase in cardiovascular events compared to conventional risk. Not only did CAC predict outcomes more accurately, it improved compliance with preventive therapy and lifestyle recommendations 73e77…”
Section: Evaluation Of Acute But Low Risk Chest Pain In the Emergencymentioning
confidence: 99%
“…CVD is currently the leading cause of death from disease in military populations1 and is a frequent cause of discharges on medical grounds 2 3. It is hoped that detecting disease while the individual remains asymptomatic will ultimately translate into lower rates of death from these diseases.…”
Section: Why Screening Is Perceived Necessarymentioning
confidence: 99%
“…These frequently latent diseases are prevalent in approximately 3 per 1000 members of the general population5 though phenotypical penetrance is incomplete and only a proportion of these people suffer symptoms. The majority of deaths in populations similar to the Armed Forces are associated with physical exertion, such as that seen in military training and occur more frequently in male populations, such as the British Army 3. In 80% of the deaths the first manifestation of the underlying disease is the terminal event, so waiting for symptoms to develop is also not an effective alternative option.…”
Section: Why Screening Is Perceived Necessarymentioning
confidence: 99%